Performance Assessment of Sintered Metal Fiber Filters in Fluid Catalytic Cracking Unit - Liang Yang; Zhongli Ji; Qiaoqi Xu; Hao Li (International Journal of Chemical Engineering)
A long-term test was performed in a fluid catalytic cracking (FCC) hot gas filtration facility using sintered metal candle filters. The operating temperature and pressure were maximum 55°C and 0.28 MPa, respectively. Specific particle sampling systems were used to measure the particle size and concentration directly at high temperature. The range of inlet particle concentration is from 150 to 165 mg/Nm3. The outlet particle concentration is in the range of 0.71–2.77 mg/Nm3 in stable operation. The filtration efficiency is from 98.23% to 99.55%. The inlet volume median diameter and the outlet volume median diameter of the particle are about 1 μm and 2.2 μm, respectively. The cake thickness is calculated based on the equation of Carman-Kozeny. The effects of operating parameters including face velocity, gas cleaning pressure, pulse duration, and maximum pressure drop were investigated. The optimal operating conditions and cleaning strategies were determined. The results show that sintered metal fiber filters are suitable for industrial application due to the good performance and high efficiency observed.